2002
DOI: 10.1097/00003246-200202000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance in the intubated human airway is an indicator of optimal gas conditioning

Abstract: Inspired gas at body temperature and saturated is thermodynamically neutral to the intubated airway, and thus may be considered the optimal condition for ventilation lasting more than a few hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 9 publications
0
24
0
3
Order By: Relevance
“…In premature infants, a study from the pre-surfactant, pre-antenatal steroid era found that in infants of <1,500 g ventilated with low-humidity gases of <36.5°C in temperature, respiratory morbidity was greater than in those ventilated with warmer, high-humidity gases [18]. Although the lower airway adds to gas conditioning [6], adult studies suggest that gases for endotracheal ventilation should be conditioned to 37°C and 100% RH to minimise the workload [19]. The ISO (International Organisation for Standardisation) specifies that for all patients with an artificial airway, humidifiers must deliver an absolute humidity of ≥33 mg H 2 O/l [7].…”
Section: Discussionmentioning
confidence: 99%
“…In premature infants, a study from the pre-surfactant, pre-antenatal steroid era found that in infants of <1,500 g ventilated with low-humidity gases of <36.5°C in temperature, respiratory morbidity was greater than in those ventilated with warmer, high-humidity gases [18]. Although the lower airway adds to gas conditioning [6], adult studies suggest that gases for endotracheal ventilation should be conditioned to 37°C and 100% RH to minimise the workload [19]. The ISO (International Organisation for Standardisation) specifies that for all patients with an artificial airway, humidifiers must deliver an absolute humidity of ≥33 mg H 2 O/l [7].…”
Section: Discussionmentioning
confidence: 99%
“…Optiflow (Fisher & Paykel Healthcare, Auckland, New Zealand) is a new nasal high-flow (NHF) oxygen system that allows the delivery of up to 60 L/min of heated and humidified, blended air and oxygen via wide-bore nasal cannula. The system conditions the inspired gas to 37°C and 44 mg H 2 O/L, which is considered thermodynamically neutral to the airway, 3 preserving the function of the ciliated mucosa. 4 Recent work described complications associated with unhumidified high-flow face mask (HFFM) oxygen therapy, which include discomfort and airway drying.…”
Section: Introductionmentioning
confidence: 99%
“…Rathgeber et al [22] [26,29].Es kann also sowohl zu Unterbefeuchtung als auch zu Überbefeuchtung kommen.…”
Section: Methodenvergleichunclassified